PREDICTORS OF EARLY INITIATION OF BREASTFEEDING (EIBF) IN SULAWESI ISLAND: A POPULATION-BASED STUDY: Prediktor Praktik Inisiasi Menyusui Dini (IMD) pada Ibu di Pulau Sulawesi - Rimawati Aulia Insani Sadarang; Bs. Titi Haerana (Universitas Airlangga, 2023)
Background: Early initiation of breastfeeding (EIBF) is pivotal to the success of exclusive breastfeeding and plays an important role not only in reducing infection-related neonatal mortality but also in providing protection in the next period of life. Purpose: This study aims to identify predictive factors of early breastfeeding practices on Sulawesi Island. Methods: A cross-sectional study based on population by using data from the Indonesia Demographic and Health Surveys (IDHS) in 2017 was conducted on 1,040 women who had given live birth in 6 provinces on Sulawesi Island. The analysis used bivariate and multivariate logistic regression with predictive models for complex sample design, adjusted for confounders to examine the relationship of EIBF with independent variables. Results: The study showed that 50.58% of women practiced EIBF on Sulawesi Island. Significantly, and adjusted for confounder, it found the predictive factors of EIBF practice consecutively, singleton birth being the factor with the highest association value (aOR:11.35, 95%CI (0.00-0.07)), skin-to-skin contact (aOR:3.05,95%CI (2.22–4.21)), normal delivery (aOR:2.94, 95%CI (1.94–4.45)) and delivery accompanied by family (aOR: 1.68,95% CI (1.06–2.67)) and parity factor >1 (aOR: 1.52,95% CI (1.10–2.10)). Conclusion: The fulfillment of education related to the urgency of implementing EIBF to pregnant women and their families as a support system as well as the application of standard operating procedure for EIBF for all types of deliveries in health facilities is vital to support the successful implementation of EIBF.